1958
DOI: 10.1063/1.1723333
|View full text |Cite
|
Sign up to set email alerts
|

Electron Recombination Coefficient Measurements in Nitrogen at Low Pressures

Abstract: Articles you may be interested inGlobal rate coefficients for ionization and recombination of carbon, nitrogen, oxygen, and argon Phys. Plasmas 19, 073515 (2012); 10.1063/1.4737147Retardingfield analyzer for measurements of ion energy distributions and secondary electron emission coefficients in lowpressure radio frequency discharges Rev.solution near the germanium-indium interface is not saturated, until equilibrium conditions are established. This nonsaturated condition can therefore differentiate between at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1961
1961
1970
1970

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Its formation probably is due to N + N02 -* N20 + O (47) Using presently accepted values for specific rates of subsequent reactions, a value for fc4s of 1.7 X 10-14 wras deduced.…”
Section: Reactions Of Active Nitrogenmentioning
confidence: 98%
See 1 more Smart Citation
“…Its formation probably is due to N + N02 -* N20 + O (47) Using presently accepted values for specific rates of subsequent reactions, a value for fc4s of 1.7 X 10-14 wras deduced.…”
Section: Reactions Of Active Nitrogenmentioning
confidence: 98%
“…The difference in values obtained in regular and active nitrogen was explained on the basis of long-lived molecular ions originating in the discharge. Some of the earlier observations in active nitrogen have been attributed to the presence of molecular ions (21,47). Ionization of NO during the recombination of nitrogen atoms (with the NO as the third body) also has been advanced as the electron source (94).…”
Section: Theories Of Active Nitrogenmentioning
confidence: 99%
“…As.a consequence, many of the previous recombination studies may not apply to the ion assumed to be present, e.g., N2 + , leading to much confusion in the literature. [7][8][9][10][11][12][13] In several of the reported nitrogen recombination studies 11 " 15 the measurements have been extended over a range of temperatures. Most of these studies were conducted without the benefit of mass analysis or any a priori knowledge concerning the identity of the dominant ion species.…”
mentioning
confidence: 99%
“…It is now believed, for example, that dissociative recombination may sometimes be a rapid process with a rate coefficient of the order of 10 -• cm•/sec [Bates, 1950], and that ion-atom interchanges may occur with rate coefficients as large as 10-' cm'/sec [Dalgarno, 1961]. On the other hand, nonresonant, asymmetric charge-transfer reactions are expected to be comparatively slow at thermal energies with rate coefficients typically less than 10-" Many workers [Biondi and Brown, 1949;Bryan et al, 1957;Faire et al, 1958;Faire and Champion, 1959;Bromer, 1960;ZipS, 1961;Kasner et al, 1961;Mentzoni, 1963;Kasner and Biondi, 1964] have reported values for the volume recombination coefficient in nitrogen. In some of these experiments the effects of diffusion [Gray and Kerr, 1962] were not taken into account, so that the reported values substantially overestimate the magnitude of the recombination coefficient.…”
Section: •Rg(z) = G •• N(n2 +) D•' (3)mentioning
confidence: 99%